2017
DOI: 10.18632/oncotarget.16894
|View full text |Cite
|
Sign up to set email alerts
|

Histone demethylase JMJD3 regulates CD11a expression through changes in histone H3K27 tri-methylation levels in CD4+ T cells of patients with systemic lupus erythematosus

Abstract: Aberrant CD11a overexpression in CD4+ T cells induces T cell auto-reactivity, which is an important factor for systemic lupus erythematosus (SLE) pathogenesis. Although many studies have focused on CD11a epigenetic regulation, little is known about histone methylation. JMJD3, as a histone demethylase, is capable of specifically removing the trimethyl group from the H3K27 lysine residue, triggering target gene activation. Here, we examined the expression and function of JMJD3 in CD4+ T cells from SLE patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…KDM6B (or JMJD3) is known to affect activation of germinal center B cells and their differentiation into plasma cells ( Barwick et al., 2018 ), which was shown to occur in this study. This demethylase activity has also been reported for development of rheumatoid arthritis and lupus ( Jia et al., 2018 ; Yin et al., 2017 ). In contrast, DNMT1 promotes DNA methylation by transferring methyl groups to DNA specific CpG structures and is important for T-cell homeostasis ( Lee et al., 2001 ) and regulating B-cell activation ( Lai et al., 2013 ).…”
Section: Discussionsupporting
confidence: 67%
“…KDM6B (or JMJD3) is known to affect activation of germinal center B cells and their differentiation into plasma cells ( Barwick et al., 2018 ), which was shown to occur in this study. This demethylase activity has also been reported for development of rheumatoid arthritis and lupus ( Jia et al., 2018 ; Yin et al., 2017 ). In contrast, DNMT1 promotes DNA methylation by transferring methyl groups to DNA specific CpG structures and is important for T-cell homeostasis ( Lee et al., 2001 ) and regulating B-cell activation ( Lai et al., 2013 ).…”
Section: Discussionsupporting
confidence: 67%
“…We also found that probiotics increased the osteoblastic activity by downregulating miRNA-138 that regulates the aberrant H3K27me3 methylation mark within the promoter region of Tfam. Histone modifications are significant regulators of epigenetic chromatin remodeling and are found to activate gene transcription 48 effectively. Histone 3 lysine 27 methylation 3 (H3K27me3) is one of the critical posttranslational modifications of histones.…”
Section: Discussionmentioning
confidence: 99%
“…JMJD3 is known as a H3K27 demethylase, which regulates the transcription of target genes through H3K27me3 demethylation [ 53 ]. A previous study showed that JMJD3 synergistically regulated the transcription of target genes with the transcription regulator NF-ĪŗB/p65 [ 27 ] and emerging evidences demonstrated that NF-ĪŗB/p65 was associated with the development of sepsis [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%